The problems faced by First-grade intermediate students in studying the Arabic language - Fleeh Hassan, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The research aims at identifying the problems faced by First-grade intermediate students in studying the Arabic language, through answering the following question: What are the problems of studying the Arabic language from students’ perspective? The research is limited to First-grade intermediate students of the year (2017-2018) in Intermediate and Secondary schools in Baghdad governorate in Al-Karkh III. Research procedures: The research consisted of (28) intermediate, Secondary schools, and (37) students of first grade intermediate. The researchers scouted the opinions of some students out of 120, which involved the problems faced by students in learning the Arabic language. The researchers categorized the problems that had been reached through exploring sure students and their parents in (33) categories in a questioner for each student. They draw out the validity of the questioner by presenting it to experts who assured its stability of each question written in the questioner. The questioner was applied to the research sample that consists of (120) students from (8) intermediate and Secondary schools in Al-Karkh III. The data were processed statistically by using correlation coefficient Pearson, weight, and percentage mean. Results of the research: The critical problems that faced First grade, intermediate students in studying the Arabic language are: The Arabic language book category: There is a shortage of solved exercises. The Arabic language subject is new to intermediate students. The content of the Arabic language book concentrates on knowledge and understanding levels while neglecting other levels. Arabic language teachers’ category: The teacher cannot enrich the subject with examples. The teacher neglects text scripts. Student's category: The given hours are not sufficient to cover the whole book. Applied style and ways of teaching category: Teaching aids that suites the given subjects are rare. The teacher faces obstacles in using the suitable way of teaching. Examination techniques category: The shortage of variety in forming Arabic language questions. The researchers concluded that in students’ opinion, the Arabic language is the most challenging subject compared to others, and they recommended the necessity of establishing training courses not to be less than one course every three years, that is for assessing Arabic language teachers with up-to-date information in new strategies, techniques and ways of teaching. They suggested a relevant study would handle the problems faced by First-grade intermediate students in studying the Arabic language.